Sistem Pakar Diagnosis Penyakit Mata Menggunakan Metode Naive Bayes - Panggabean, achmad Juniardo (JATISI, 2025)
Eye diseases are health disorders that can lead to a decline in quality of life and even blindness if not treated early. This study aims to develop a web-based expert system for diagnosing eye diseases using the Naive Bayes method. The system is designed to identify the type of disease based on symptoms selected by the user. Testing was conducted on 30 patient data cases, and the system achieved a 100% match rate—30 out of 30 cases were consistent with the expert's diagnosis. This demonstrates that the Naive Bayes method is effective for classifying eye diseases. The system was developed using PHP, MySQL, and CodeIgniter 3. The results show that the system is capable of providing fast, efficient, and accurate diagnoses and can serve as an alternative tool for early self-diagnosis of eye diseases